2020
DOI: 10.1016/j.engstruct.2020.111289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bi-directional loading on the seismic performance of C-shaped piers of core walls

Abstract: Reinforced concrete structural walls are commonly used as the primary lateral load resisting system in modern buildings constructed in high seismic regions. Most walls in high-rise buildings are C-shaped to accommodate elevators or other architectural features. C-shaped walls have complex loading and response including: (1) symmetric response in the direction of the web, (2) asymmetric response in the direction of the flange and (3) high compression and shear demands when used as a pier in a coupled-wall confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Several experimental studies have been reported on nonplanar (flanged) RC walls under bi‐directional loading 2–11 . In their experimental study on U‐shaped walls, Ile and Reynouard 4 observed up to 33% reduction of displacement capacity due to bi‐directional loading effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies have been reported on nonplanar (flanged) RC walls under bi‐directional loading 2–11 . In their experimental study on U‐shaped walls, Ile and Reynouard 4 observed up to 33% reduction of displacement capacity due to bi‐directional loading effect.…”
Section: Introductionmentioning
confidence: 99%
“…F I G U R E 1 Unexpected failure modes observed in RC walls, (A, B) lateral instability in Chile 13 and (C) New Zealand, 14 (D) concrete spalling at web to boundary element interface, 15 (E) out-of-plane shear-axial failure of a slender wall, 16 and (F) diagonal web crushing of a slender wall 14 Several experimental studies have been reported on nonplanar (flanged) RC walls under bi-directional loading. [2][3][4][5][6][7][8][9][10][11] In their experimental study on U-shaped walls, Ile and Reynouard 4 observed up to 33% reduction of displacement capacity due to bi-directional loading effect. They concluded that a pre-existing displacement in the transverse direction reduces the maximum attainable strength in U-shaped walls.…”
mentioning
confidence: 99%
“…the most recent five works, to the Authors' knowledge, are Lucchini et al (2022); Gwalani et al (2021); Salami et al (2021); Zhang and Tao (2021); Opabola et al (2020)), shear walls (e.g. the most recent five works, to the Authors' knowledge, are Wang et al (2023Wang et al ( , 2022; Niroomandi et al (2021); Behrouzi et al (2020); Beyer et al (2008)). Generally, tested specimens were not shear-critical thus similarities with respect to beam-column joints are difficult to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Te shear wall with a reasonable design of the wall limb section shows good stifness, which can efectively resist winds, earthquakes, and other horizontal efects. Compared with the conventional rectangular section reinforced concrete shear wall, it can only provide one translational stifness [7]. While the U-shaped cross-sectional shear wall can provide the stifness needed for two translational directions of the structure and has excellent seismic performance, it is recognized that it has good marketing in both high-rise buildings and large space buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Beyer et al [8] performed quasi-static cyclic tests on two U-shaped reinforced concrete walls, which provided a theoretical basis for studying the seismic performance of U-shaped walls and formulating appropriate design guidelines. Behrouzi et al [7] tested three large C-shaped walls under unidirectional and bidirectional loads. It was found that the C-shaped wall has a symmetric response in the web direction and an asymmetric response in the fange direction.…”
Section: Introductionmentioning
confidence: 99%